Chitosan Alginate Nanoparticles of Protein Hydrolysate from Acheta domesticus with Enhanced Stability for Skin Delivery - Kankanit Yeerong; Panuwan Chantawannakul; Songyot Anuchapreeda; Saranya Juntrapirom; Watchara Kanjanakawinkul; Anette Müllertz; Thomas Rades; Wantida Chaiyana (MDPI AG, 2024)
This study aimed to develop chitosan alginate nanoparticles (CANPs) for enhanced stability for dermal delivery of protein hydrolysate from Acheta domesticus (PH). CANPs, developed using ionotropic pre-gelation followed by the polyelectrolyte complex technique, were characterized for particle size, polydispersity index (PDI), and zeta potential. After the incorporation of PH into CANPs, a comprehensive assessment included encapsulation efficiency, loading capacity, morphology, chemical analyses, physical and chemical stability, irritation potential, release profile, skin permeation, and skin retention. The most optimal CANPs, comprising 0.6 mg/mL sodium alginate, 1.8 mg/mL calcium chloride, and 0.1 mg/mL chitosan, exhibited the smallest particle size (309 ± 0 nm), the narrowest PDI (0.39 ± 0.01), and pronounced negative zeta potential (−26.0 ± 0.9 mV), along with an encapsulation efficiency of 56 ± 2%, loading capacity of 2.4 ± 0.1%, release of 40 ± 2% after 48 h, and the highest skin retention of 12 ± 1%. The CANPs induced no irritation and effectively enhanced the stability of PH from 44 ± 5% of PH remaining in a solution to 74 ± 4% after three-month storage. Therefore, the findings revealed the considerable potential of CANPs in improving PH stability and skin delivery, with promising applications in cosmetics and related fields.